2021
DOI: 10.2215/cjn.04830421
|View full text |Cite
|
Sign up to set email alerts
|

When and How Is It Possible to Stop Therapy in Patients with Lupus Nephritis

Abstract: Glucocorticoids and other immunosuppressants still represent the cornerstone drugs for the management of SLE (Systemic Lupus Erythematosus) and lupus nephritis. The refined use of these drugs over the years has allowed to obtain stable disease remission and improvement of the long-term kidney and patient survival. Nevertheless, a prolonged use of immunosuppressive agents may be accompanied by severe and even life-threatening side effects. Theoretically, a transient or even definitive withdrawal of immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Indeed, in a national survey,22 55% of physicians managing patients with LN reported continuing low-dose corticosteroids in maintenance. WIN-Lupus was not a trial of complete treatment withdrawal, as reported in recent cohort studies 4. One of the possible reasons for clinicians to maintain IST is to prevent the need for corticosteroid use or increase,34 which is itself associated with significant damage 35 36.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, in a national survey,22 55% of physicians managing patients with LN reported continuing low-dose corticosteroids in maintenance. WIN-Lupus was not a trial of complete treatment withdrawal, as reported in recent cohort studies 4. One of the possible reasons for clinicians to maintain IST is to prevent the need for corticosteroid use or increase,34 which is itself associated with significant damage 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…WIN-Lupus was not a trial of complete treatment withdrawal, as reported in recent cohort studies. 4 One of the possible reasons for clinicians to maintain IST is to prevent the need for corticosteroid use or increase, 34 which is itself associated with significant damage. 35 36 Here, the overall exposure to corticosteroids did not differ between the groups, indicating that IST discontinuation did not lead to a compensatory increase in corticosteroid dose for lupus containment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, SLE is treated with the application of biological agents, which provide relief and minimize the use of glucocorticoids [ 7 ]. SLE patients still require long-term drug-based maintenance, which often has toxic side effects [ 8 ]. Long-term use of glucocorticoids can even lead to emotional disorders such as depression in patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%